Histopathological assessment of prognostic factors in pancreatic resection specimens using a standardised protocol - Silvanto, A.; Balamurugan, T.; Bagwan, I.N. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
Background. Adenocarcinoma involving the pancreas shows differences in prognostic parameters including resection margin statusdepending on subtype.Aim: To assess the reported incidence of each type and the rate of R1 resection using detailed histopathological examination protocol.Methods. All pancreaticoduodenectomies between June 2011 and June 2013 at our institute were analysed. These were classified accordingto the site of origin, R1 status, size, stage at resection, lymph node status and the rate of lymphovascular and perineural invasion.Results. 58 adenocarcinomas included 23 ductal, 16 intraductal papillary mucinous neoplasm (IPMN) related, 8 duodenal, 7 ampullaryand 4 distal common bile duct (CBD) tumours. The CBD, pancreatic ductal and IPMN-related adenocarcinomas had the highest rates of R1resection, at 75%, 69.5 and 62.5%, with the posterior and SMV margins most frequently involved. Ampullary adenocarcinoma had lowerrates of R1 resection (14%) as well as perineural invasion (0%).Conclusion. Ampullary adenocarcinomas had a lower rate of R1 resection and perineural invasion, both of which are parameters associatedwith a poorer outcome. This correlates with literature indicating ampullary tumours have a better prognosis. Our study also highlights thehigh rate of detection of microscopic margin involvement when a detailed histopathological examination protocol is employed.